2018
DOI: 10.1098/rsos.171075
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of Banert cascade reaction

Abstract: Computational inside of Banert cascade reaction for triazole formation is studied with B3LYP/6-31G(d,p) level of theory. The reaction proceeds mainly by SN2 initial chloride displacement rather than SN2′-type attack. Furthermore, according to the rate of reaction calculation, SN2 displacement is much faster than SN2′ displacement in the order of 8. The [3,3]-sigmatropic rearrangement for the conversion of propargyl azide into triazafulvene has been proved as the rate-determining step having highest activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…For the azides investigated here, neither the allenyl azide nor the triazafulvene intermediate were directly observed as an intermediate by 1 H NMR. This is consistent with a computational model of this cascade, which predicts a rate determining barrier for the initial sigmatropic process (Scheme , [3,3]) and a fast electrocyclization (Scheme a, step i) …”
Section: Results and Discussionsupporting
confidence: 89%
“…For the azides investigated here, neither the allenyl azide nor the triazafulvene intermediate were directly observed as an intermediate by 1 H NMR. This is consistent with a computational model of this cascade, which predicts a rate determining barrier for the initial sigmatropic process (Scheme , [3,3]) and a fast electrocyclization (Scheme a, step i) …”
Section: Results and Discussionsupporting
confidence: 89%
“…This is followed by a 6-π electrocyclization and a nucleophilic trap to generate NH-1,2,3-triazoles. 239 Recently, Sharpless and co-workers explored this rearrangement and developed a general method for generating NH-1,2,3trizoles (Scheme 45b). 240 Substituted 1,2,3-triazoles can be generated via a CuAAC reaction, but using HN 3 would be unappealing to generate NH-1,2,3-trizoles.…”
Section: Propargyl Azidesmentioning
confidence: 99%
“…32,33 Currently, only one theoretical study about the sigmatropic pathway mechanism of the Banert cascade has been reported. 34 In that work, the [3,3]-sigmatropic rearrangement for the conversion of propargylic azide into triazafulvene has been proved as the rate determining step. Therefore, we wanted to study the Banert cascade to provide the theoretical basis of the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%